Boston Consulting Group Strategy Analysis on Siber Nusantara Publisher - Hapzi; Farhan Saputra (Greenation International Journal of Economics and Accounting, 2025)
This study aims to analyze the strategic position and formulate an appropriate marketing strategy for Siber Nusantara Publisher in facing the increasingly competitive scientific publishing industry. This study uses a descriptive qualitative approach with a strategic analysis method through the integration of the Boston Consulting Group (BCG) Matrix and SWOT analysis. Research data were obtained from documentation studies, observations, and secondary data analysis related to the growth of scientific publications and the market share of academic publishers. The results show that Siber Nusantara Publisher is in the Question Mark quadrant in the BCG Matrix, which is characterized by a high market growth rate but a relatively low market share. This condition indicates that the institution has significant growth opportunities in the scientific publishing industry but requires a more aggressive marketing strategy to increase market share and strengthen competitiveness. The managerial implications of this study emphasize the importance of implementing a development strategy (build strategy) through strengthening editorial quality, utilizing digital technology in journal management, and expanding academic networks to improve the reputation and sustainability of Siber Nusantara Publisher in the scientific publication ecosystem.